UJI AKTIVITAS ANTIOKSIDAN EKSTRAK KASARAIR BUNGA KECOMBRANG (Etlingera elatior) SEBAGAI BAHAN PANGAN FUNGSIONAL - Dede Sukandar; Nani Radiastutu; Ira Jayanegara; Anna Muawanah; Adeng Hudaya (Research Center for Chemistry - LIPI, 2011)
A research of antioksidant activity from water crude extract of kecombrang flower (Etlingera elatior) have been reported. This Research aim to give erudite evidence of kecombrang flower as a functional food. Antioksidant was examined by activity diphenyl picryl hidrazyl ( DPPH) methode and chemicalcomponent analyses using GCMS. Water crude extract of kecombrang flower shows antioxidan activity ( ICso = 61. 6497 ppm) and waspredicted to have component of l-dodekanol, S-metil-l-oxo-lbuten 1-(21,41, 51-trihidroxyl phenil and 1tetradecene (tR= 13,26, area=6,03, similarity at 98%).Keyword: Kecombrang ( Etlingera elatior), functional food, antioxidant